Cell Adhesion Molecules and Their Roles and Regulation in the Immune and Tumor Microenvironment - Harjunpää, Heidi; Llort Asens, Marc; Guenther, Carla; Fagerholm, Susanna C. (Frontiers in Immunology, 2019)
The immune system and cancer have a complex relationship with the immune system playing a dual role in tumor development. The effector cells of the immune system can recognize and kill malignant cells while immune system-mediated inflammation can also promote tumor growth and regulatory cells suppress the anti-tumor responses. In the center of all anti-tumor responses is the ability of the immune cells to migrate to the tumor site and to interact with each other and with the malignant cells. Cell adhesion molecules including receptors of the immunoglobulin superfamily and integrins are of crucial importance in mediating these processes. Particularly integrins play a vital role in regulating all aspects of immune cell function including immune cell trafficking into tissues, effector cell activation and proliferation and the formation of the immunological synapse between immune cells or between immune cell and the target cell both during homeostasis and during inflammation and cancer. In this review we discuss the molecular mechanisms regulating integrin function and the role of integrins and other cell adhesion molecules in immune responses and in the tumor microenvironment. We also describe how malignant cells can utilize cell adhesion molecules to promote tumor growth and metastases and how these molecules could be targeted in cancer immunotherapy.